Pricing and Hedging of Contingent Credit Lines - Loukoianova, Elena (IMF Working Papers; Working Paper ;, 2006)
Contingent credit lines (CCLs) are widely used in bank lending and also play an important role in the functioning of short-term capital markets. Yet, their pricing and hedging has not received much attention in the finance literature. Using a financial engineering approach, the paper analyzes the structure of simple CCLs, examines methods for their pricing, and discusses the problems faced in hedging CCL portfolios.